Masuknya Amerika Serikat Sebagai Anggota ASEAN+8 - Harsiwi, Resti Dwi (Global and Policy Journal of International Relations, 2013)
ABSTRACTASEAN which is constructed based on the cultural similiarity and the identity along with the vision and mission to develop and growing the area of ASEAN, make the ASEAN members needs more fund to fulfill the building project and developing the infrastructure. Since there are capability lacknesses of these ASEAN members, especially the financial matter causing the ASEAN need more help from other countries which are not belongs to ASEAN member. The United State of America joining in ASEAN +8 does giving much contribute in ASEAN, but as the time goes by, many countries think that The United State of America joining in ASEAN +8 not for fulfilling the ASEAN needs only, but also to fulfill the needs of United State of America from the ASEAN+8.Keywords: ASEAN+8, United State of America Capability, the needs of United State of AmericaDOI:https://doi.org/10.33005/jgp.v1i02.1999